SYNERGETIC EFFECTS OF VX-680 AND CURCUMIN COMBINATION ON CANCER CELLS - Nhung, Bach Thi Hoai Phuong, Nguyen Dac Tu, Bui Thi Van Khanh, To Thanh Thuy, Hoang Thi My Nhung (Tạp chí Sinh lý học Việt Nam, 2022)
Objective: to check if the combination of VX-680 and Curcumin could synergistically induce the anti-tumor effect in three cancer cell lines MCF-7, HeLa, and H1299. Methods: xCelligence system was used to determine the IC50 values, doubling time, and cell behavior. Results: the combination of VX-680 and Curcumin inhibited the proliferation of three cancer cell lines with smaller IC50 values compared to that of the VX-680 and Curcumin alone. Moreover, the mixture led to a significantly higher perturbation rate of the cell cycle than the separate compound. Conclusion: Taken together, VX-680 and Curcumin could be used together to enhance the effect of these compounds on cancer cells.